Pengaruh Bauran Pemasaran Islami Terhadap Keputusan Pembelian Hijab Di Big Mall Samarinda - Sarnining Sarnining; Muhammad Iswadi; Yusran Yusran (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Abstract The purpose of this study is to determine the product, price, place, and promotion partially and simultaneously have a significant effect on purchasing decisions for hijab at Big Mall Samarinda. This study uses quantitative methods because it emphasizes testing theories through measuring research variables by analyzing data with statistical procedures. In this study, four variables X and Y variables were used, namely the product variable (X1), price (X2), place (X3), promotion (X3), and purchase decision (Y). The types of data used in this study are primary and secondary data. The sampling method used is by using the Cochran formula with a sample of 100 respondents. The method of data collection in this study used observation, questionnaires/questionnaires and documentation. The data analysis technique in this study uses a validity test, reliability test, classical assumption test consisting of (normality test, multicollinearity, heteroscedasticity, linearity, and autocorrelation), and multiple linear regression analysis test consisting of (t test, F test, and test R). The results of this study indicate that the product variable partially has a significant effect on purchasing decisions with a significant value of 0.043 ≤ 0.05, the price variable partially has no significant effect on purchasing decisions with a significant value of 0.733 ≥ 0.05, the place variable partially has a significant effect on decisions. purchases with a significant value of 0.000 ≤ 0.05, the promotion variable partially has a significant effect on purchasing decisions with a significant value of 0.000 ≤ 0.05. The results of this study indicate that the product, price, place, and promotion variables simultaneously have a significant effect on purchasing decisions with a significant value of 0.000 ≤ 0.05. The effect of all variables in this study was 73.4% while 26.6% was influenced by other variables. Keywords: Islamic Marketing Mix on Purchase Decision